Effect of Organic Fertilizer (Cow Manure and Chicken Dung) Application on Growth and Yield of Mungbean (Vigna radiata L.) - Sammah, Merhama M.; Ammad, Sharnalyn K.; Baki, Munib J.; Aming, Milda M.; Kairan, Fernalyn H.; Murphy, Aldimar S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Mungbean (Vigna radiata L.) is a useful legume with short maturity and nitrogen-fixing capacity, which makes it suitable for poor farmers. In Sulu Province, it is of cultural importance as a vegetable crop and valued for medicinal value. But as demand has increased with expanding populations, so has its decline in production. In response, a field experiment was carried out from August 11 to November 25, 2021, at the Mindanao State University – Sulu, College of Agriculture Demo Farm. The research tested the impacts of organic fertilizers—cow manure and chicken dung—on Mungbean performance under Randomized Complete Block Design (RCBD) with three treatments and four replications. Results indicated that chicken dung significantly increased the yield and growth of the crop and resistance to the Mosaic Virus compared to cow dung. The outcome of these findings indicates the promise of chicken dung as a good organic fertilizer for improving Mungbean productivity and promoting sustainable agriculture.